Estudio comparado de la gestión académica en modalidad presencial y virtual de la maestría Tecnología de la Información, ESPAM MFL - Viteri Santos, María Juley (2022)
The objective of the research was based on developing a comparative study of the virtual and face-to-face modality of the master's degree in Information Technology at ESPAM MFL for the strengthening of an efficient, effective and efficient hybrid academic management. For the collection of information, bibliographical, field and descriptive research was used, in addition to the deductive, inductive and analytical method for gathering information to verify the components involved. Likewise, an interview was applied to obtain timely and necessary information about the processes that are handled in the master's degree in TI and a survey of the students of the III cohort of the master's degree. The research procedure had three phases, the first consisted of identifying the processes of academic management of the master's degree in TI at ESPAM MFL, then the achievements and difficulties that academic management has presented in both virtual and face-to-face modalities were diagnosed and finally, an action plan for an efficient, effective and effective hybrid academic management was developed. It was evidenced that, in terms of the depth reached in the contents of the subjects in the master's degree in TI, in the face-to-face modality the students assimilate that it is excellent, unlike the virtual one that is accentuated as very good, that is, it leaves the excellence, but still maintains a high level of qualification